2009
DOI: 10.1128/aac.00417-09
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpesvirus Replication by 5-Substituted 4′-Thiopyrimidine Nucleosides

Abstract: A series of 4-thionucleosides were synthesized and evaluated for activities against orthopoxviruses and herpesviruses. We reported previously that one analog, 5-iodo-4-thio-2-deoxyuridine (4-thioIDU), exhibits good activity both in vitro and in vivo against two orthopoxviruses. This compound also has good activity in cell culture against many of the herpesviruses. It inhibited the replication of herpes simplex virus type 1 (HSV-1), HSV-2, and varicella-zoster virus with 50% effective concentrations (EC 50 s) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Regarding TK, C or G insertions/deletions in homopolymer repeats, evidenced in 13 isolates, and the changes R221H and C336Y have previously been implicated in many ACV-resistant HSV strains (21,24,37,40,41,47). Moreover, this study described new amino acid changes in TK potentially related to ACV resistance: A207P, L170P, and Y53D in HSV-1 isolates 1, 2, and 3, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding TK, C or G insertions/deletions in homopolymer repeats, evidenced in 13 isolates, and the changes R221H and C336Y have previously been implicated in many ACV-resistant HSV strains (21,24,37,40,41,47). Moreover, this study described new amino acid changes in TK potentially related to ACV resistance: A207P, L170P, and Y53D in HSV-1 isolates 1, 2, and 3, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…For combined efficacy and animal studies, strains E-377 and MS were used to evaluate efficacy against HSV-1 and HSV-2, respectively. The provenance and phenotypic and genotypic characteristics of each of these viruses were reported recently (26). Mutations in these isolates thought to confer resistance to ACV are in the TK open reading frame.…”
Section: Methodsmentioning
confidence: 99%
“…Other laboratories have demonstrated the inhibitory potential of 5-substituted 4=-thiopyrimidine nucleoside derivatives against poxviruses (27,29), despite the fact that the narrow substrate specificity of poxvirus TK remains a challenge for selecting potent nucleoside analogues. Our study demonstrated that OPVs (VACVs, CPXVs, and CML1) are efficiently inhibited by KAY-2-41 in vitro at concentrations in the submicromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, a series of 5-substituted 2=-deoxy-4=-thiopyrimidine nucleosides was also shown to retain good antiviral activity against some herpesviruses, with the 2=-deoxy-5-ethyl-4=-thiouridine derivative being the most potent against alphaherpesviruses (28). The antiviral efficacy of 5-substituted 4=-thiopyrimidine against alphaherpesviruses and OPVs was reported in two studies (27,29). The compound 5-iodo-4=-thio-2=-deoxyuridine (4=-thioIDU) inhibited both VACV and CPXV replication at concentrations in the nanomolar range (27).…”
mentioning
confidence: 99%